2017
DOI: 10.1111/ijlh.12675
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between red blood cell distribution width, bilirubin, and clinical characteristics of patients with gastric cancer

Abstract: Our study indicated that RDW and bilirubin could be potential prognostic factors for patients of GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…RDW has obtained increasing attention in recent years, particularly in tumor field. [ 17 20 ] In our study, we evaluated the prognostic role of RDW in patients undergoing curative resection for nonmetastic rectal cancer. Based on the multivariate analysis, we found that elevated RDW-cv is associated with poor DFS (HR = 1.56, P = .010) and elevated RDW-sd can predict poor OS (HR = 1.70, P = .009).…”
Section: Discussionmentioning
confidence: 99%
“…RDW has obtained increasing attention in recent years, particularly in tumor field. [ 17 20 ] In our study, we evaluated the prognostic role of RDW in patients undergoing curative resection for nonmetastic rectal cancer. Based on the multivariate analysis, we found that elevated RDW-cv is associated with poor DFS (HR = 1.56, P = .010) and elevated RDW-sd can predict poor OS (HR = 1.70, P = .009).…”
Section: Discussionmentioning
confidence: 99%
“…In a study including 366 GC patients, Hirahara et al demonstrated that stage, CEA, and RDW were independent prognostic factors for OS [26]. In another study including 144 GC patients, RDW was found to be higher than in the healthy control group and increased RDW values were found to be associated with advanced stage [12]. In addition, Yazıcı et al showed that high RDW was associated with advanced GC and short DFS/OS times [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, RDW has been shown to be associated with poor prognosis in cardiovascular, pulmonary, and hepatic diseases, and it also has been shown to be associated with outcomes in malignant diseases [9,10]. High RDW values have been found as associated with poor prognosis in many cancers such as lung, breast, and GC [11,12]. In addition to all these biomarkers, recently introduced another potential inflammatory marker is the HB-RDW ratio (HRR).…”
Section: Introductionmentioning
confidence: 99%
“…Wei and colleagues [ 24 ] reported that higher RDW levels were significantly higher in the gastric cancer patients than in normal population. Ay and colleagues [ 25 ] reported that RDW levels in patients with colon cancer were significantly higher than its level in patients with colon polyp.…”
Section: Discussionmentioning
confidence: 99%